Mean-field description of collapsing and exploding Bose-Einstein condensates - Adhikari, Sadhan K. [UNESP] (American Physical Society (APS), 2002)
Numerical simulations based on the time-dependent mean-field Gross-Pitaevskii equation was performed to explain the dynamics of collapsing and exploding Bose-Einstein condensates (BEC) of 85Rb atoms. The atomic interaction was manipulated by an external magnetic field via a Feshbach resonance. On changing the scattering length of atomic interaction from a positive to a large negative value, the condensate collapsed and ejected atoms via explosion.
Keywords: Atomic beams; Computer simulation; Electron resonance; Magnetic field effects; Molecules; Rubidium; Scattering; Bose-Einstein condensates; Atomic physics